1912
DOI: 10.1002/cber.191204502156
|View full text |Cite
|
Sign up to set email alerts
|

Über krystallisierte Polysaccharide aus Stärke

Abstract: Der B a d . A n i l i n -u n d S o d a f a b r i k spreche ich fur die bereitwillige oberlassung verschiedener Ausgangsmaterialien rneinen besten Dank aus.Die Arbeit wurde im Chemisch-technischen Dr. G. S c h u l t z ) der Technischen Hochschule z u Laboratorium (Prof. Munchen ausgefuhrt. 327.Hans Pringsheim und Alfred Langhans: dber krystallisierte Polysaccharide aus Stllrke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

1913
1913
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 1 publication
3
3
0
1
Order By: Relevance
“…He reported higher yields of β-dextrin from glycogen crude preparations of amylopectin, and this is the reason why he postulated that amylose was polymerized α-diamylose, and amylopectin and glycogen were polymerized β-triamylose. Like Schardinger, Pringsheim observed that the relative proportions of α-and β-dextrins depended on the different substrates used (Pringsheim and Langhans 1912). Pringsheim described the chemical behavior of dextrins and their properties, in agreement with the previous results published by Schardinger.…”
Section: Cyclodextrin Chemistrysupporting
confidence: 81%
“…He reported higher yields of β-dextrin from glycogen crude preparations of amylopectin, and this is the reason why he postulated that amylose was polymerized α-diamylose, and amylopectin and glycogen were polymerized β-triamylose. Like Schardinger, Pringsheim observed that the relative proportions of α-and β-dextrins depended on the different substrates used (Pringsheim and Langhans 1912). Pringsheim described the chemical behavior of dextrins and their properties, in agreement with the previous results published by Schardinger.…”
Section: Cyclodextrin Chemistrysupporting
confidence: 81%
“…In the hands of Pringsheim, Schardinger’s observations on the formation of crystalline decomposition products of starch under the action of B. macerans mainly led to the elaboration of a possible interpretation of the chemical structure of amylose and of amylopectin. For Pringsheim, the Schardinger dextrins arose through the bacterial depolymerization of starch to the fundamental units: the amylose fraction being broken down into the α-series of dextrins (polyamyloses) and the amylopectin fraction being degraded to the β-series. For over 20 years, Pringsheim and his various collaborators (Alfred Langhans, Franz Eissler, Stefanie Lichtenstein, Walter Persch, Diamandi Dernikos, Kurt Goldstein, Arthur Beiser, Arnold Steingroever, Alfred Wiener, Alexander Weidinger, Eugen Schapiro, James Irvine, Paul Meyersohn) penned an abundant literature on their studies of dextrins, although the studies suffered from numerous errors due to the use of dextrins that were not pure and to problems arising from separation of the fractions and from the use of unsuitable analytical methods (e.g., determination of the masses by cryoscopy).…”
Section: The Period Of Doubt: 1911–1935mentioning
confidence: 99%
“…Cyclodextrins (CDs) were discovered and identified over a century ago [1][2][3]. Between 1911 and 1935, Pringsheim and co-workers demonstrated the ability of CDs to form complexes with many organic molecules [4,5]. Since the 1970s, the structural elucidation of the three natural CDs, α-, β-, and γ-CDs composed of 6-, 7-, and 8-membered α-D-glucopyranoses linked by α-1,4 glycosidic bonds, allowed the development and the rational study of their encapsulation properties [6,7].…”
Section: Introductionmentioning
confidence: 99%